The emperor's code - Korman, Gordon (New York : Scholastic, 2010)
Amy and Dan are separated while trying to retrieve a clue which is guarded by thousands of soldiers and worry they cannot succeed apart.
Includes cards.
Wilson's Junior High School, October 2010.
Horn Book, October 2010.
Wilson's Junior High School.
Horn Book.
5.1
Keywords: Families -- History -- Juvenile fiction; Cryptography -- Juvenile fiction; Genealogy -- Juvenile fiction; Family life -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery and detective stories; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Ciphers -- Fiction; Family secrets -- Fiction; Mystery and detective stories; China -- Fiction; Code and cipher stories; Mystery fiction